Bolt and method for manufacturing the bolt

JP7630336B2Active Publication Date: 2025-02-17NIPPON STEEL CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021061945
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-17
Estimated Expiration
2041-03-31

Smart Images

  • Figure 0007630336000009
    Figure 0007630336000009
  • Figure 0007630336000010
    Figure 0007630336000010
  • Figure 0007630336000011
    Figure 0007630336000011
Patent Text Reader

Abstract

To provide a bolt made of austenite ferrite duplex stainless steel having no risk of breaking at a neck part and excellent in corrosion resistance.SOLUTION: A bolt made of an austenite-ferrite duplex stainless steel is adopted, which contains C, Si, Mn, P, S, N, Ni, Cr, Mo, and Cu, and the balance of Fe and impurities, has Md30 of -150°C to 200°C, and a head and shank, a ferritic phase at a shank of 20.0 to 65.0%, and when the following test method is performed, a fracture site is generated in a site that was a thread part or that was the shank part where the thread part is not provided before test piece processing. (Test method) Grind a bearing surface of a bolt head while leaving a shaft diameter or an outer diameter of the threaded part from a center axis, a test piece having a height of 50% or more and 80% or less of the head height before polishing is manufactured, and the tensile test specified in JIS B 1054:2013 is performed on the test piece.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a bolt and a method for manufacturing a bolt, and more particularly to a bolt made of austenitic-ferritic duplex stainless steel and a method for manufacturing a bolt. [Background technology]

[0002] As materials for high-strength bolts, austenitic stainless steel such as SUS304 or martensitic precipitation hardening stainless steel such as SUS630 are used.

[0003] For example, Patent Document 1 describes a high-strength bolt made of austenitic stainless steel with a high total content of C and N. Patent Document 2 describes a high-strength bolt made of martensitic stainless steel containing about 13% Cr, which is excellent in manufacturability and cost.

[0004] In addition, in severe corrosive environments such as exposure to seawater or brackish water, the use of high-strength bolts made of duplex stainless steel consisting of ferrite-austenite phases, which have good corrosion resistance, is being considered.

[0005] Meanwhile, austenitic-ferritic duplex stainless steel (hereinafter sometimes simply referred to as "duplex stainless steel") is known to have high strength. Therefore, when duplex stainless steel is processed into, for example, a bolt with a large diameter, cracks may occur due to workability issues. In addition, while the strength is further increased by work hardening during processing, there is also a possibility that the entire bolt may become brittle. Furthermore, it is also possible that the neck of the bolt (hereinafter referred to as "neck"), where stress is most likely to concentrate during use, may be more likely to break. Here, the neck of the bolt refers to the boundary between the head and the shaft.

[0006] Patent Document 3 describes an austenite-ferritic duplex stainless steel wire for bolts that solves the above problems, has excellent corrosion resistance and workability, and is less likely to break at the neck, and a bolt using the same. The bolt described in Patent Document 3 has a Vickers hardness of 150 or more between the maximum hardness and the minimum hardness from a position 1.0 mm from the tip of the bolt head on the central axis of the bolt cross section to the end.

[0007] However, depending on the bolt shape and forging method, it may be difficult to satisfy the above hardness conditions even with steel types of similar chemical composition, and fracture may occur in the neck. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2006-274295 A [Patent Document 2] JP 2005-179718 A [Patent Document 3] JP 2019-178381 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a bolt made of austenitic-ferritic duplex stainless steel that is free from the risk of fracture at the neck and has excellent corrosion resistance, and a method for manufacturing the bolt. [Means for solving the problem]

[0010] The present invention has been made to solve the above-mentioned problems, and its gist is a bolt made of an austenitic-ferritic duplex stainless steel and a method for manufacturing a bolt as described below.

[0011] [1] A bolt made of austenitic-ferritic duplex stainless steel, The chemical composition of the austenitic-ferritic duplex stainless steel is, in mass%, C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05-2.00%, Al: 0-0.30%, Nb: 0-0.50%, Ti: 0 to 0.25%, Co: 0-1.00%, Ca: 0 to 0.0050%, Mg: 0 to 0.0050%, B: 0~0.0040%, V: 0~1.00%, Zr: 0-0.02%, Ta: 0 to 0.07%, W: 0 to 1.00%, Sn: 0-1.00%, REM: 0~0.050%, The balance is composed of Fe and impurities. Md shown in the following formula (1) 30 is -150℃~200℃, The bolt has a head and a shaft, and a thread is provided on at least a part or the entirety of the shaft, The ferrite phase in the metal structure at the center of the shaft portion is 20.0 to 65.0% by volume, A bolt that, when subjected to the test method described below, breaks at the threaded portion or at a portion of the shank that did not have a threaded portion before the test specimen was processed. (Test Method) The bearing surface of the head of the bolt is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion intact, and a test piece is produced in which the distance between the ground surface and the tip of the head is in the range of 50% to 80% of the height of the head before grinding, and a tensile test specified in JIS B 1054:2013 is performed on the test piece. Md30(℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(1) In the above formula (1), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. [2] A bolt made of austenitic-ferritic duplex stainless steel, The chemical composition of the austenitic-ferritic duplex stainless steel is, in mass%, C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05 to 3.00%, Cu: 0.05 to 2.00% Furthermore, Al: 0.01 to 0.30%, Nb: 0.01 to 0.50%, Ti: 0.05 to 0.25%, Co: 0.02-1.0%, Ca: 0.0005 to 0.0050%, Mg: 0.0005~0.0050%, B: 0.0001~0.0040%, V: 0.03 to 1.00%, Zr: 0.003~0.02%, Ta: 0.01 to 0.07%, W: 0.05 to 1.00%, Sn: 0.005 to 1.00%, and REM: 0.005~0.050%, Contains one or more selected from The balance is composed of Fe and impurities. Md shown in the following formula (2) 30 is -150℃~200℃, The bolt has a head and a shaft, and a thread is provided on at least a part or the entirety of the shaft, The ferrite phase in the metal structure at the center of the shaft portion is 20.0 to 65.0% by volume, A bolt that, when subjected to the test method described below, breaks at the threaded portion or at a portion of the shank that did not have a threaded portion before the test specimen was processed. (Test Method) The bearing surface of the head of the bolt is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion intact, and a test piece is produced in which the distance between the ground surface and the tip of the head is in the range of 50% to 80% of the height of the head before grinding, and a tensile test specified in JIS B 1054:2013 is performed on the test piece. Md30(℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(2) However, each element symbol in the above formula (2) represents the content (mass%) of each element contained in the steel, and if the element is not contained, it is set to zero. [3] The bolt described in [1] or [2], characterized in that in a cross section parallel to the central axis of the bolt and including the central axis, the difference between the maximum hardness and the minimum hardness from a position 1.0 mm from the tip of the head to the end of the shank on the central axis is less than 150 in Vickers hardness. [4] Chemical composition, in mass percent: C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05 to 3.00%, Cu: 0.05-2.00%, Al: 0-0.30%, Nb: 0-0.50%, Ti: 0 to 0.25%, Co: 0-1.00%, Ca: 0 to 0.0050%, Mg: 0 to 0.0050%, B: 0~0.0040%, V: 0~1.00%, Zr: 0-0.02%, Ta: 0 to 0.07%, W: 0 to 1.00%, Sn: 0-1.00%, REM: 0~0.050%, The balance is composed of Fe and impurities. Md shown in the following formula (1) 30 is -150℃~200℃, A step of wiredrawing a forging austenite-ferrite duplex stainless steel wire having a ferrite phase in a metal structure of 20.0 to 65.0% by volume; and a step of heating the steel wire after the wire drawing process to 50°C or more and 300°C or less and then warm forging the steel wire into a bolt material having a head and a shaft. [1] How bolts are manufactured. Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(1) In the above formula (1), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero. [5] Chemical composition, in mass percent: C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05 to 2.00% Furthermore, Al: 0.01 to 0.30%, Nb: 0.01 to 0.50%, Ti: 0.05 to 0.25%, Co: 0.02-1.0%, Ca: 0.0005 to 0.0050%, Mg: 0.0005~0.0050%, B: 0.0001~0.0040%, V: 0.03 to 1.00%, Zr: 0.003~0.02%, Ta: 0.01 to 0.07%, W: 0.05 to 1.00%, Sn: 0.005 to 1.00%, and REM: 0.005~0.050%, Contains one or more selected from The balance is composed of Fe and impurities. Md30 represented by the following formula (2) is -150°C to 200°C, A step of wiredrawing a forging austenite-ferrite duplex stainless steel wire having a ferrite phase in a metal structure of 20.0 to 65.0% by volume; and a step of heating the steel wire after the wire drawing process to 50°C or more and 300°C or less and then warm forging the steel wire into a bolt material having a head and a shaft. [2] How bolts are manufactured. Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(2) However, each element symbol in the above formula (2) represents the content (mass%) of each element contained in the steel, and if the element is not contained, it is set to zero. [6] A method for manufacturing a bolt described in [4] or [5], using forging austenitic-ferritic duplex stainless steel wire having a diameter of 6.5 mm or more. Effect of the Invention

[0012] According to the present invention, it is possible to provide a bolt which is free from the risk of fracture at the neck and has excellent corrosion resistance, and a manufacturing method thereof. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram showing a bolt according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating a method for preparing a test piece in the test method. [Diagram 3] FIG. 3 is a cross-sectional view of a bolt according to an embodiment of the present invention, illustrating the positions at which hardness differences are measured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present inventors have investigated the reason why bolts made of duplex stainless steel are prone to fracture at the neck, and have obtained the following findings. The following description will be given with reference to FIG. 1. The bolt shown in FIG. 1 comprises a head 1 and a shank 11. A threaded portion 4 is provided on the surface of the shank 11 near the end. Meanwhile, the head 1 side of the shank 11 is a cylindrical portion 3 that has no threaded portion. That is, the shank 11 shown in FIG. 1 has a threaded portion 4 formed on a part thereof. The boundary between the cylindrical portion 3 of the shank 11 and the head 1 is the neck 2. Reference numeral 1a denotes the bearing surface of the head.

[0015] As shown in FIG. 1(a), the strength of the head 1 and threaded portion 4 of a bolt produced by bolt processing, which has a high degree of processing, increases, but the increase in strength of the cylindrical portion 3 is small because the degree of processing is low.

[0016] (b) Even if stress is concentrated at the neck 2, which is the boundary between the head 1 and the cylindrical portion 3, fracture is unlikely to occur at the neck 2 if there is a difference in strength between the head 1 and the cylindrical portion 3. This is thought to be because the material of the cylindrical portion 3 itself has not been processed and therefore has a large amount of elongation, so even if stress is concentrated at the neck 2, the material of the cylindrical portion 3 is stretched, making fracture unlikely to occur.

[0017] (c) When an austenitic-ferritic duplex stainless steel wire (hereinafter referred to as duplex stainless steel wire) is processed into a bolt through wire drawing or the like, work hardening occurs and the strength increases, as with other steel wires. However, since the duplex stainless steel wire is originally strong, it is difficult for a difference in strength to occur between the head portion 1 and the cylindrical portion 3, so the overall strength is high and breakage is likely to occur at the neck portion 2.

[0018] (d) When processing the duplex stainless steel wire into a bolt, it is necessary to appropriately control the chemical composition, metal structure, etc. so as to create an appropriate strength difference between the head 1 and the cylindrical portion 3.

[0019] (e) When the duplex stainless steel wire is processed into a bolt, a part of the austenite phase is transformed to form deformation-induced martensite. Therefore, in order to generate an appropriate strength difference between the head portion 2 and the cylindrical portion 3 as described above, it is necessary to adjust the absolute amount of the austenite phase that transforms into the deformation-induced martensite phase.

[0020] (f) Furthermore, the amount of deformation-induced martensite phase is affected not only by the absolute amount of the austenite phase as described above, but also by the stability of the austenite phase. The stability of the austenite phase also depends on the content of added elements such as C, N, Si, and Mn. For this reason, it is necessary to appropriately control the chemical composition and adjust the stability of the austenite phase.

[0021] (g) Generally, when the head of a bolt is formed by forging, traces of metal flow may be found in the metal structure of the head after forging. When the neck of a bolt breaks during a tensile test, the crack often propagates along the metal flow of the head.

[0022] (h) Therefore, the inventors discovered that the risk of neck fracture can be clarified by performing a tensile test on the bolt with the bearing surface scraped off and the end of the metal flow exposed. Furthermore, if no neck fracture occurs in this test, it can be determined that the neck fracture will not occur in the finished bolt.

[0023] (i) It was found that even if the neck of a bolt manufactured by cold forging a steel wire breaks when the above test is performed, if the same steel wire is heated at a low temperature and then forged (warm forging) to produce a bolt, the neck of the bolt will not break in the above test.

[0024] The present invention has been made based on the above findings. The bolt and the method for manufacturing the bolt according to the present embodiment will be described below.

[0025] Before describing the bolt of this embodiment, austenitic-ferritic duplex stainless steel wire rod for forging, which is the material for the bolt of this embodiment, will be described. The austenitic-ferritic duplex stainless steel wire rod for forging according to the present embodiment has a chemical composition, in mass%, of C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06 to 0.40%, Ni: 1.5 to 8.5%, Cr: 19.0 to 29.0%, Mo: 0.05 to 3.00%, Cu: 0.05 to 2.00%, Al: 0~0.30%, Nb: 0~0.50%, Ti: 0~0.25%, Co: 0~1.00%, Ca: 0~0.0050%, Mg: 0~0.0050%, B: 0~0.0040%, V: 0~1.00%, Zr: 0~0.02%, Ta: 0~0.07%, W: 0~1.00%, Sn: 0~1.00%, REM: 0~0.050%, balance: Fe and impurities, and Md 30 The temperature is -150°C to 200°C, and the ferrite phase in the metal structure is 20.0 to 65.0% by volume. Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(1) In the above formula (1), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.

[0026] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."

[0027] C: 0.080% or less C is an element necessary for increasing strength. However, if the C content exceeds 0.080%, Cr carbides are generated, and corrosion resistance is deteriorated. Therefore, the C content is set to 0.080% or less, preferably 0.060% or less, and more preferably 0.030% or less. On the other hand, since an extreme reduction in the C content leads to a significant increase in costs, the C content is preferably 0.001% or more, and more preferably 0.008% or more.

[0028] Si:2.50% or less Silicon is an element necessary for deoxidation. However, if the content of silicon exceeds 2.50%, the toughness is deteriorated. Therefore, the silicon content is set to 2.50% or less, preferably 2.00% or less, more preferably 1.00% or less, and even more preferably 0.80% or less. On the other hand, in order to obtain the above-mentioned effect, the silicon content is preferably 0.01% or more, more preferably 0.05% or more, even more preferably 0.10% or more, and even more preferably 0.20% or more.

[0029] Mn: 0.01 to 5.50% Mn increases the austenite phase in duplex stainless steel, inhibits the formation of processing-induced martensite, and improves toughness. It also has the effect of increasing the solid solubility of nitrogen. For this reason, the Mn content is set to 0.01% or more. On the other hand, if the Mn content exceeds 5.50%, the corrosion resistance decreases and it may be difficult to secure a specified proportion of ferrite phase in the metal structure. For this reason, the Mn content is set to 5.50% or less. The Mn content is preferably more than 2.00% and less than 3.00%.

[0030] P:0.040% or less P is an impurity element contained in steel and deteriorates hot workability. For this reason, the P content is set to 0.040% or less, and preferably 0.030% or less. On the other hand, since an extreme reduction in the P content significantly increases the manufacturing cost, the P content is preferably 0.001% or more.

[0031] S: 0.030% or less Like P, S is an impurity contained in steel, and reduces hot workability, toughness, and corrosion resistance. For this reason, the S content is set to 0.030% or less, more preferably 0.005% or less, and even more preferably 0.002% or less. On the other hand, since reducing the S content drastically increases costs, the S content is preferably 0.0001% or more.

[0032] N: 0.06~0.40% N dissolves in the austenite phase to increase strength and corrosion resistance, and also increases the austenite phase in duplex stainless steel. For this reason, the N content is set to 0.06% or more, and preferably 0.1% or more. On the other hand, if the N content exceeds 0.40%, the cold forgeability decreases, and the proportion of the ferrite phase in the metal structure may decrease. For this reason, the N content is set to 0.40% or less, and preferably 0.20% or less.

[0033] Ni: 1.5~8.5% Ni is an element that increases the austenite phase in duplex stainless steel, and is necessary to ensure the austenite phase in the composition system of the present invention. It also suppresses the formation of processing-induced martensite and improves toughness. In addition, Ni is effective in ensuring corrosion resistance against various acids. For this reason, the Ni content is 1.5% or more, and preferably exceeds 3.0%. On the other hand, Ni is an expensive metal, and if it is contained in excess, the proportion of the ferrite phase in the metal structure decreases. For this reason, the Ni content is 8.5% or less, and preferably less than 5.5%.

[0034] Cr: 19.0~29.0% Cr is necessary to ensure corrosion resistance. Cr is also effective in suppressing the formation of processing-induced martensite. For this reason, the Cr content is set to 19.0% or more, preferably 20.0% or more, and more preferably 20.5% or more. On the other hand, Cr is an element that increases the ferrite phase, and if it is contained in excess of 29.0%, the ferrite phase becomes excessive, decreasing the corrosion resistance and toughness. For this reason, the Cr content is set to 29.0% or less, preferably 28.0% or less, and more preferably 24.0% or less.

[0035] Mo: 0.05 to 3.00% Mo is effective in improving the corrosion resistance of stainless steel. Therefore, the Mo content is set to 0.05% or more, and preferably 0.12% or more. On the other hand, since an excessive Mo content increases the manufacturing cost, the Mo content is set to 3.00% or less, preferably 2.00% or less, and more preferably less than 2.00%.

[0036] Cu: 0.05-2.00% Like Ni, Cu increases the austenite phase in duplex stainless steel and suppresses the formation of processing-induced martensite. Cu is also an effective element for improving toughness and corrosion resistance to various acids. For this reason, the Cu content is set to 0.05% or more, and preferably 0.20% or more. On the other hand, if Cu is contained in excess of 2.00%, it impairs hot workability. For this reason, the Cu content is set to 2.00% or less, preferably 1.50% or less, and more preferably less than 1.00%.

[0037] In addition to the above elements, the duplex stainless steel wire rod of the present embodiment may contain one or more elements selected from Al, Nb, Ti, Co, Ca, Mg, B, V, Zr, Ta, W, Sn, and REM. The lower limit of the content of these elements is 0% or more. The reasons for limiting each element will be explained below.

[0038] Al: 0 to 0.30% Al is an element used for deoxidizing steel. Therefore, it may be contained as necessary. However, if the Al content exceeds 0.30%, it impairs the toughness of the base material. Therefore, the Al content is set to 0.30% or less, and preferably 0.10% or less. On the other hand, in order to obtain the above effect, the Al content is preferably 0.01% or more.

[0039] Ti: 0 to 0.25% By including Ti, the adverse effect of C and / or S on the corrosion resistance can be suppressed. Therefore, Ti may be included as necessary. However, if Ti is included in excess, the toughness is reduced, so the Ti content is set to 0.25% or less, and preferably 0.20% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably 0.05% or more, and more preferably 0.07% or more.

[0040] Nb: 0 to 0.50% By including Nb in the same manner as Ti, the adverse effect of C and / or S on the corrosion resistance can be suppressed. Therefore, Nb may be included as necessary. However, if Nb is included in excess, toughness is reduced, so the Nb content is set to 0.50% or less, and preferably 0.40% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably 0.01% or more, more preferably 0.10% or more, and more preferably 0.20% or more.

[0041] Co: 0 to 1.00% Co is an effective element for increasing the toughness and corrosion resistance of steel. Therefore, it may be contained as necessary. However, even if Co is contained in an amount exceeding 1.00%, the effect is saturated and the manufacturing cost increases. Therefore, the Co content is set to 1.0% or less, and preferably 0.50% or less. On the other hand, in order to obtain the above effect, the Co content is preferably 0.02% or more, and more preferably 0.10% or more.

[0042] Ca: 0 to 0.0050% Ca is an element that improves the hot workability of steel. Therefore, it may be contained as necessary. However, if an excessive amount of Ca is contained, it actually deteriorates the hot workability. Therefore, the Ca content is set to 0.0050% or less, and preferably 0.0040% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably 0.0005% or more, and more preferably 0.001% or more.

[0043] Magnesium: 0 to 0.0050% Like Ca, Mg is an element that improves the hot workability of steel. Therefore, Mg may be contained as necessary. However, excessive Mg content rather reduces the hot workability. Therefore, the Mg content is set to 0.0050% or less, and preferably 0.0040% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably 0.0005% or more, and more preferably 0.001% or more.

[0044] B: 0~0.0040% B is an element that improves the hot workability of steel. Therefore, it may be contained as necessary. However, if an excessive amount of B is contained, it actually deteriorates the hot workability. Therefore, the B content is set to 0.0040% or less, and more preferably 0.0025% or less. On the other hand, in order to obtain the above effect, the B content is preferably 0.0001% or more, and more preferably 0.0005% or more.

[0045] V: 0~1.00% V has the effect of suppressing the formation of Cr carbonitrides and improving corrosion resistance. Therefore, it may be contained as necessary. However, even if V is contained excessively, the effect is saturated and cold forging cracks may occur. Therefore, the V content is set to 1.00% or less, and more preferably 0.80% or less. On the other hand, in order to obtain the above effect, the V content is preferably 0.03% or more, and more preferably 0.10% or more.

[0046] Zr: 0 to 0.02% Zr has the effect of suppressing the deterioration of corrosion resistance caused by C or S. Therefore, it may be contained as necessary. However, if Zr is contained excessively, toughness decreases. Therefore, the Zr content is set to 0.02% or less, and preferably 0.015% or less. On the other hand, in order to obtain the above effect, the Zr content is preferably 0.003% or more, and more preferably 0.005% or more.

[0047] Ta: 0 to 0.07% Ta, like Zr, has the effect of suppressing the deterioration of corrosion resistance caused by C and / or S. Therefore, it may be contained as necessary. However, if Ta is contained excessively, toughness decreases. Therefore, the Ta content is set to 0.07% or less, and preferably 0.05% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably 0.01% or more, and more preferably 0.02% or more.

[0048] W: 0~1.00% W has the effect of improving corrosion resistance. Therefore, it may be contained as necessary. However, if W is contained excessively, the manufacturing cost increases, so the W content is set to 1.00% or less, and preferably 0.80% or less. On the other hand, in order to obtain the above effect, the W content is preferably 0.05% or more, and more preferably 0.10% or more.

[0049] Sn: 0 to 1.00% Sn is effective in improving acid resistance. Therefore, it may be contained as necessary. However, if Sn is contained excessively, it reduces hot workability. Therefore, the Sn content is set to 1.00% or less, and preferably 0.80% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably 0.005% or more, and more preferably 0.01% or more.

[0050] REM: 0~0.050% Like Ca, REM is an element that improves the hot workability of steel. Therefore, REM may be contained as necessary. However, excessive REM content rather reduces hot workability. For this reason, the REM content is set to 0.050% or less, and preferably 0.040% or less. On the other hand, in order to obtain the above effect, the REM content is preferably 0.005% or more, and more preferably 0.01% or more.

[0051] Here, REM is a collective term for 17 elements, including 15 lanthanoid elements, Y, and Sc. One or more of these 17 elements can be contained in steel, and the REM content means the total content of these elements.

[0052] In the chemical composition of this embodiment, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.

[0053] 2.Metal structure 2-1. Volume fraction of ferrite phase in the metal structure of duplex stainless steel wire Next, the metal structure of the duplex stainless steel wire rod of this embodiment will be described. Austenite phase in the metal structure is partially transformed into processing-induced martensite phase during the subsequent wire drawing and bolt processing. Processing-induced martensite has high strength, but if its ratio is excessive, it will cause breakage at the bolt neck. For this reason, the duplex stainless steel wire rod of this embodiment should have a volume ratio of the ferrite phase, which does not transform during processing, within a preferred range. Specifically, in the steel wire rod according to the present invention, the volume ratio of the ferrite phase to the total volume of the structure is set to 20.0% or more in the austenite-ferrite two-phase structure. Since the austenite phase is prevented from transforming into martensite and hardening during processing by warm forging, the austenite phase can be relatively increased, that is, the ferrite phase can be relatively reduced. The volume ratio of the ferrite phase to the total volume is preferably 37.0% or more, more preferably 40.0% or more.

[0054] On the other hand, if the volume ratio of the ferrite phase to the whole is excessive, a bolt having the desired strength cannot be obtained, so the volume ratio of the ferrite phase is set to 65.0% or less, preferably 63.0% or less, and more preferably 60.0% or less.

[0055] The volume fraction of the ferrite phase is determined by mirror-polishing a cross section perpendicular to the longitudinal direction of the steel wire including the central axis, electrolytically etching the cross section in an oxalic acid solution, coloring the ferrite phase, and calculating the area fraction by image analysis. It is known that the "volume fraction" and the "area fraction" are equal in quantitative metallography. Therefore, in this embodiment, the calculated area fraction is the volume fraction. The range of the image analysis is 200 x 250 μm.

[0056] 2-2. Stability of martensite structure As described above, a part of the austenite phase transforms into the stress-induced martensite phase. The transformation from austenite to stress-induced martensite varies depending on the elements contained, and the left-hand side value of the following equation (2) is used as an index.

[0057] Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(2) However, each element symbol in the above formula (2) represents the content (mass%) of each element contained in the steel, and if the element is not contained, it is set to zero.

[0058] If the value of the left side of the above formula (2) is less than -150°C, the austenite phase will be stabilized, making it difficult for the processing-induced martensite phase to form, and the strength of the cold-worked (thread-rolled) thread surface will be inferior, making cracks more likely to occur in the stress-concentrated areas of the thread roots. For this reason, the value of the left side of formula (2) is set to -150°C or higher, preferably -140°C or higher, and more preferably -130°C or higher.

[0059] On the other hand, if the value of the left side of formula (2) exceeds 200°C, the phase stability of the austenite phase decreases, and it becomes easier to transform into the martensite phase. As a result, forging becomes difficult because of the increased distortion. Increasing the forging temperature makes processing easier, but there is a limit to setting the temperature high because it leads to changes in the metal structure at high temperatures and increased costs. In addition, the volume fraction of the martensite phase after processing becomes excessive, which reduces ductility and makes it easier for fracture to occur at the bolt neck. For this reason, the value of the left side of formula (2) is set to 200°C or less, preferably 170°C or less, and more preferably 150°C or less.

[0060] 3. Diameter of steel wire In this embodiment, the diameter of the duplex stainless steel wire before drawing is preferably 6.5 mm or more. The diameter of the duplex stainless steel wire is preferably 7.0 mm or more, more preferably 12.0 mm or more, and even more preferably 14.0 mm or more. The diameter of the duplex stainless steel wire is preferably 20.0 mm or less, and more preferably 16.0 mm or less. In this embodiment, the duplex stainless steel wire is a steel material hot-rolled into a rod shape, and includes a steel material wound into a coil shape, including so-called "bar in coil". The duplex stainless steel wire mainly refers to the above duplex stainless steel wire that has been subjected to cold working such as wire drawing, and includes a coil-shaped one.

[0061] Next, the bolt of this embodiment will be described. The bolt of this embodiment is made of steel having the same chemical composition as the above-mentioned duplex stainless steel wire rod, and has Md 30 The temperature range is -150°C to 200°C. The bolt of this embodiment has a head and a shank. The ferrite phase in the metal structure at the center of the shank is 20.0 to 65.0% by volume. The center of the shank may be either the central shank of the cylindrical portion or the central shank of the threaded portion.

[0062] The volume ratio of the ferrite phase at the center of the shaft portion is determined by exposing a longitudinal section parallel to the central axis direction of the shaft portion and including the central axis, mirror-polishing the longitudinal section, electrolytically etching the section in an oxalic acid solution, coloring the ferrite phase, and calculating the area ratio by image analysis. In this embodiment, the calculated area ratio is the volume ratio. The target range of the image analysis is a range with a width of 200 μm centered on the central axis and a length of 250 μm along the longitudinal direction of the central axis. The target range of the image analysis may be the region of the cylindrical portion or the region of the threaded portion.

[0063] As described below, the bolt of this embodiment is a bolt manufactured by wire drawing and warm forging the above-mentioned duplex stainless steel wire, and as shown in FIG. 1, has a head 1 and a shank 11, with a threaded portion 4 provided on at least a part or all of the shank 11.

[0064] The bolt according to this embodiment is not limited to the one shown in FIG. 1, but may be a bolt in which a threaded portion is provided over the entire shaft portion 11 shown in FIG.

[0065] In the bolt of this embodiment, when the following test method is carried out, the fracture occurs at the threaded portion or at a portion that was a shank portion without a threaded portion before the test specimen was processed. As described below, the shank portion appears to be extended by the grinding process when preparing a test specimen from the bolt, but this extended portion is not included in the above-mentioned "portion that was a shank portion without a threaded portion before the test specimen was processed." A bolt that fractures at the extended portion is outside the scope of the present invention. In addition, "the fracture occurs at a threaded portion or at a portion that was a shank portion without a threaded portion before the test specimen was processed" has the same meaning as the standard in JIS B 1054:2013 that "the fracture must occur in the loose thread portion or cylindrical portion." It is desirable that the fracture form be a ductile fracture.

[0066] (Test Method) The bearing surface of the bolt head is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion intact, and a test piece is produced in which the distance between the ground surface and the tip of the head is in the range of 50% to 80% of the head height before grinding, and the test piece is subjected to a tensile test specified in JIS B 1054:2013.

[0067] Figure 2 illustrates how to prepare the test specimen. The bolt on the left in Figure 2 is the finished bolt, and the bolt on the right in the figure is the test specimen obtained by machining the finished bolt. In the test specimen, the bearing surface of the bolt head is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion. If the height of the bolt head as the finished product is A, and the distance between the ground surface and the tip of the head in the test specimen is B, then distance B is in the range of 50% to 80% of height A.

[0068] If the distance b is less than 50% of the height a, the strength of the head will be reduced and the head will come off due to shear fracture during a tensile test, which is undesirable. If the distance b exceeds 80% of the height a, the weak part of the head will not be exposed as an extension of the cylindrical part, and the risk of bolt neck breakage before grinding will not be detected, which is undesirable.

[0069] If, as a result of such a test, the test piece fractures in the threaded portion, or in a portion of the shank that did not have a threaded portion before the test piece was processed, the finished bolt will not fracture even if stress is applied to the neck. In other words, the bolt (test piece) on the right side of Figure 2 should fracture within the range of symbol C.

[0070] 4.Difference in hardness In general bolts, the head is formed by cold forging the steel wire obtained by drawing a duplex stainless steel wire, so the amount of processing of the head is large and the hardness increases. In addition, the threaded portion of the bolt is formed by rolling after forging, so work hardening occurs and the hardness increases. On the other hand, the hardness of the cylindrical portion of the bolt does not increase significantly before and after processing. For this reason, in general bolts, the hardness value is the largest at the head, and the hardness value is the largest at the cylindrical portion. In addition, the hardness value is the smallest at the cylindrical portion, and the hardness value is the smallest at the minimum.

[0071] However, as described below, the bolt of this embodiment has a head formed by warm forging, so that the tendency of embrittlement of the head, including the neck, can be reduced, and the increase in hardness at the head is relatively small. Furthermore, since duplex stainless steel is a material with high hardness, the increase in hardness is small even if rolling is performed to form the thread. Therefore, the bolt of this embodiment has a small difference between the maximum hardness and the minimum hardness. In this way, the bolt of this embodiment can reduce the tendency of embrittlement of the neck, so that fracture at the neck can be avoided even if the difference in hardness is small.

[0072] Specifically, in the bolt of this embodiment, in a cross section parallel to the central axis of the bolt and including the central axis, the difference between the maximum hardness and the minimum hardness from a position 1.0 mm from the tip of the head on the central axis to the end of the shank is preferably less than 150 in Vickers hardness, which can suppress breakage at the neck.

[0073] Figure 3 shows a cross section parallel to the central axis direction of the bolt and including the central axis, which is indicated by a dashed line. Hardness is measured by exposing the cross section shown in Figure 3 and performing a micro Vickers hardness test every 0.5 mm from the tip of the bolt head to the end of the bolt along the central axis indicated by the dashed line, and determining the maximum and minimum hardness.

[0074] 5. Manufacturing method 5-1. Manufacturing method of duplex stainless steel wire To manufacture the duplex stainless steel wire rod of this embodiment, first, a steel ingot having the above-mentioned chemical composition is cast by a continuous casting method. The steel ingot may be made into a billet by an ingot casting method (see JIS G 0203:2009). Then, soaking and hot rolling (hot wire rolling) are performed to obtain the above-mentioned diameter. Then, the obtained steel wire rod is subjected to a solution heat treatment in a range of 900 to 1100°C for 3 to 20 minutes, and water-cooled. Then, pickling treatment is performed. In this manner, the duplex stainless steel wire rod of this embodiment is manufactured. The ferrite fraction of the steel wire rod can be adjusted to some extent by adjusting the heat treatment temperature of the solution treatment. It is sufficient to adjust the above-mentioned range so as to satisfy the ferrite fraction of this embodiment.

[0075] 5-2. Bolt manufacturing method The bolt of this embodiment includes at least a process of drawing a duplex stainless steel wire, and a process of warm forging the drawn steel wire after heating it to 50°C to 300°C. After warm forging, a threaded portion is formed to produce a bolt. Each process will be described below.

[0076] In the wire drawing process, the pickled duplex stainless steel wire is subjected to a coating treatment using oxalic acid, etc. Then, the wire is drawn at a processing rate (area reduction rate) of 5 to 25% to produce steel wire for bolts.

[0077] In the warm forging process, the drawn steel wire is heated to 50°C to 300°C and then warm forged to form a bolt material having a head and a shaft. If the temperature of the steel wire before warm forging is less than 50°C, the steel wire hardly softens, so the effect of warm forging is not obtained, which is no different from cold forging, and this is not preferable. Also, if the temperature of the steel wire before warm forging exceeds 300°C, the steel wire softens too much, which reduces the strength of the bolt after forming, which is not preferable.

[0078] When heat treatment is performed to adjust the strength of the bolt, etc., it is preferable to perform heat treatment in an oxygen-free atmosphere at 150 to 700° C. for 5 to 120 minutes after forming the threaded portion described below.

[0079] Furthermore, a thread is formed on the bolt material after warm forging. The thread can be formed, for example, by performing a rolling process on the shaft. In this manner, the bolt according to this embodiment is manufactured.

[0080] Furthermore, if necessary, the bolt may be subjected to surface polishing, etc. If surface polishing is not performed, the bolt may be subjected to surface treatment by shot blasting, followed by baking of the paint.

[0081] As described above, the duplex stainless steel wire of the present embodiment is a material for a bolt that is free from the risk of fracture at the neck and has excellent corrosion resistance. The bolt of the present embodiment is also a bolt that is free from the risk of fracture at the neck and has excellent corrosion resistance. Furthermore, according to the method for manufacturing a bolt of the present embodiment, a bolt that is free from the risk of fracture at the neck and has excellent corrosion resistance can be manufactured. EXAMPLES

[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0083] Steels having the chemical compositions shown in Tables 1A and 1B were melted in a 300 kg vacuum melting furnace and cast into billets with a diameter of 178 mm. The billets were hot-rolled to produce hot-rolled steel wires with diameters of 6.5 mm to 21.0 mm. The hot-rolling end temperature was 1050°C. Subsequently, the wires were held at any temperature between 900°C and 1100°C for 20 to 60 minutes as a solution heat treatment, and then water-cooled. For the same type of steels with different ferrite fractions, the ferrite fraction was arbitrarily changed by controlling the temperature during the solution heat treatment. That is, Test No. 74, in which the ferrite fraction was more than 65.0 volume%, was heat-treated at a temperature of more than 1100°C, and Test Nos. 65 and 75, in which the ferrite fraction was less than 20.0 volume%, were heat-treated at a temperature of less than 900°C. Then, the wires were pickled to obtain duplex stainless steel wires shown in Tables 2A and 2B. The pickling was performed by immersing the specimen in hydrochloric acid and then in a mixed acid of 1% HF and 10% HNO3 for 5 minutes.

[0084] Next, the duplex stainless steel wire was subjected to a coating treatment using oxalic acid, and then subjected to cold wire drawing to produce steel wire for bolt products as shown in Tables 2A and 2B. Tables 2A and 2B show the wire drawing ratios during wire drawing.

[0085] The volume fraction of the ferrite phase was measured for the obtained duplex stainless steel wire. The volume fraction of the ferrite phase was measured by mirror-polishing the longitudinal section of the duplex stainless steel wire, electrolytically etching the section perpendicular to the longitudinal direction of the steel wire in an oxalic acid solution to color the ferrite phase, and calculating the area fraction by image analysis.

[0086] In addition, a tensile test was performed on the duplex stainless steel wire rod to measure the tensile strength based on JIS Z 2241: 2011. The test piece used for the tensile test was a No. 14A shape.

[0087] Next, the steel wire for the bolt product after wire drawing was heated to a predetermined temperature by induction heating and then forged to form a bolt material having a head and a shaft. Furthermore, a threaded portion was formed by rolling the shaft portion of the bolt material. The threaded portion was formed near the end of the shaft portion, and the unthreaded portion was made into a cylindrical portion. In this manner, the bolt was manufactured. The bolt shape was in accordance with the JIS B 1180 standard. When the obtained bolt was subjected to heat treatment, the heat treatment was performed in an oxygen-free atmosphere at 150 to 700°C for 5 to 120 minutes.

[0088] The bolts No. 1 to 77 produced were subjected to tensile tests based on JIS B 1054:2013, in the same way as the duplex stainless steel wire rods, and their fracture locations were examined. The bolts themselves were used as test pieces for the tensile tests, and 10 bolts were tested for each test number. The tensile test was evaluated as follows: 0 bolts out of 10 that broke at the neck were marked with an "O", 1 to 9 bolts that broke at the neck were marked with an "△", and 10 bolts that broke at the neck were marked with an "X". An "O" was considered a pass.

[0089] The forgeability during forging was evaluated by the presence or absence of forging cracks after 100 pieces of hexagonal etc. were forged using a three-stage header. If there were no cracks, the piece was deemed to have passed. No. 63 and No. 74, which failed the forging test, were not subjected to any other evaluation.

[0090] The corrosion resistance of the bolts was evaluated by salt spray testing based on JIS Z 2371:2015. The corrosion resistance was evaluated based on the state of rusting after 168 hours of salt spray testing. Specifically, corrosion resistance was rated as "○" when there was no rusting or only slight spot rusting, and "×" when there was flowing rusting or overall rusting. "○" was considered a pass.

[0091] Furthermore, a hardness test was carried out on the central axis of the bolt cross section based on JIS Z 2244 (2009). The hardness test was carried out using a micro Vickers tester, measuring from 1.0 mm at 0.5 mm intervals from the tip of the bolt to the end, and the maximum and minimum hardness were calculated. The hardness was measured using a hardness tester HM-200 system manufactured by Mitutoyo Corporation.

[0092] Furthermore, the bearing surface of the bolt head was ground from the central axis while leaving the outer diameter of the cylindrical portion, to produce test specimens in which the distance between the ground surface and the tip of the head was in the range of 50% to 80% of the head height before grinding. The test specimens were then subjected to tensile tests as specified in JIS B 1054:2013. Tables 2E and 2F show the height A of the bolt head as a product, the distance B between the ground surface and the tip of the head in the test specimen, and B / A x 100(%), respectively.

[0093] The volume ratio of the ferrite phase at the center of the bolt shaft was determined by exposing a cross section parallel to the central axis of the shaft and including the central axis, mirror-polishing the cross section, electrolytically etching it in an oxalic acid solution, coloring the ferrite phase, and calculating the area ratio by image analysis. The range of the image analysis was a 200 μm wide range centered on the central axis and a 250 μm long range along the longitudinal direction of the central axis. The range of the image analysis was the cylindrical region.

[0094] The test results are summarized in Tables 1A to 2F below.

[0095] [Table 1A]

[0096] [Table 1B]

[0097] [Table 2A]

[0098] [Table 2B]

[0099] [Table 2C]

[0100] [Table 2D]

[0101] [Table 2E]

[0102] [Table 2F]

[0103] As shown in Tables 1A to 2F, the bolts of the examples of the present invention had good corrosion resistance, workability, and tensile properties, and no fracture was observed at the neck in the tensile test. On the other hand, the bolts of the comparative examples, which do not satisfy the provisions of the present invention, did not satisfy the corrosion resistance, workability, or tensile properties, and fracture was observed at the neck. [Explanation of symbols]

[0104] 1: head, 2: neck, 3: cylindrical portion, 4: threaded portion, 11: shaft portion.

Claims

1. A bolt made of austenitic-ferritic duplex stainless steel, The chemical composition of the austenitic-ferritic duplex stainless steel is, in mass%, C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05-2.00%, Al: 0-0.30%, Nb: 0 to 0.50%, Ti: 0 to 0.25%, Co: 0-1.00%, Ca: 0-0.0050%, Mg: 0 to 0.0050%, B: 0 to 0.0040%, V: 0-1.00%, Zr: 0 to 0.02%, Ta: 0-0.07%, W: 0-1.00%, Sn: 0-1.00%, REM: 0-0.050%, The balance is composed of Fe and impurities. Md represented by the following formula (1) 30 is −150° C. to 200° C., The bolt has a head and a shaft, and a thread is provided on at least a part or the entirety of the shaft, The ferrite phase in the metal structure at the center of the shaft portion is 20.0 to 65.0% by volume, A bolt that, when subjected to the test method described below, breaks at the threaded portion or at a portion of the shank that did not have a threaded portion before the test specimen was processed. (Test Method) The bearing surface of the head of the bolt is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion intact, to produce a test specimen in which the distance between the ground surface and the tip of the head is in the range of 50% to 80% of the height of the head before grinding, and a tensile test specified in JIS B 1054:2013 is performed on the test specimen. Md 30 ()=551-4462(3008)-9.23i-8.17n _13.700_29(8)+35)-18.57b_688.・・・(1) In the above formula (1), each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.

2. A bolt made of austenitic-ferritic duplex stainless steel, The chemical composition of the austenitic-ferritic duplex stainless steel is, in mass%, C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05 to 2.00%; Furthermore, Al: 0.01-0.30%, Nb: 0.01 to 0.50%, Ti: 0.05-0.25%, Co: 0.02-1.0%, Ca: 0.0005-0.0050%, Mg: 0.0005-0.0050%, B: 0.0001 to 0.0040%, V: 0.03-1.00%, Zr: 0.003 to 0.02%, Ta: 0.01 to 0.07%, W: 0.05-1.00%, Sn: 0.005 to 1.00%, and REM: 0.005-0.050%, Contains one or more selected from The balance is composed of Fe and impurities. Md represented by the following formula (2) 30 is −150° C. to 200° C., The bolt has a head and a shaft, and a thread is provided on at least a part or the entirety of the shaft, The ferrite phase in the metal structure at the center of the shaft portion is 20.0 to 65.0% by volume, A bolt that, when subjected to the test method described below, breaks at the threaded portion or at a portion of the shank that did not have a threaded portion before the test specimen was processed. (Test Method) The bearing surface of the head of the bolt is ground from the central axis while leaving the shank diameter or the outer diameter of the threaded portion intact, to produce a test specimen in which the distance between the ground surface and the tip of the head is in the range of 50% to 80% of the height of the head before grinding, and a tensile test specified in JIS B 1054:2013 is performed on the test specimen. Md 30 ()=551-4462(3008)-9.23i-8.17n _13.700_29(8)+35)-18.57b_688.・・・(2) However, each element symbol in the above formula (2) represents the content (mass%) of each element contained in the steel, and if the element is not contained, it is set to zero.

3. 3. The bolt according to claim 1 or 2, characterized in that in a cross section parallel to the central axis direction of the bolt and including the central axis, a difference between a maximum hardness and a minimum hardness from a position 1.0 mm from the tip of the head on the central axis to an end of the shank is less than 150 in Vickers hardness.

4. The chemical composition, in mass%, is C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05-2.00%, Al: 0-0.30%, Nb: 0 to 0.50%, Ti: 0 to 0.25%, Co: 0-1.00%, Ca: 0-0.0050%, Mg: 0 to 0.0050%, B: 0 to 0.0040%, V: 0-1.00%, Zr: 0 to 0.02%, Ta: 0-0.07%, W: 0-1.00%, Sn: 0-1.00%, REM: 0-0.050%, The balance is composed of Fe and impurities. Md represented by the following formula (1) 30 is −150° C. to 200° C., A step of wiredrawing an austenite-ferrite duplex stainless steel wire for forging, the metal structure of which has a ferrite phase of 20.0 to 65.0% by volume; 2. The method for manufacturing a bolt according to claim 1, further comprising a step of heating the steel wire after the wire drawing to a temperature of 50° C. or higher and 300° C. or lower, and then warm forging the steel wire into a bolt material having a head and a shaft. Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(1) In the above formula (1), each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.

5. The chemical composition, in mass%, is C: 0.080% or less, Si: 2.50% or less, Mn: 0.01 to 5.50%, P: 0.040% or less, S: 0.030% or less, N: 0.06-0.40%, Ni: 1.5-8.5%, Cr: 19.0-29.0%, Mo: 0.05-3.00%, Cu: 0.05 to 2.00%; Furthermore, Al: 0.01-0.30%, Nb: 0.01 to 0.50%, Ti: 0.05-0.25%, Co: 0.02-1.0%, Ca: 0.0005-0.0050%, Mg: 0.0005-0.0050%, B: 0.0001 to 0.0040%, V: 0.03-1.00%, Zr: 0.003 to 0.02%, Ta: 0.01 to 0.07%, W: 0.05-1.00%, Sn: 0.005 to 1.00%, and REM: 0.005-0.050%, Contains one or more selected from The balance is composed of Fe and impurities. Md represented by the following formula (2) 30 is −150° C. to 200° C., A step of wiredrawing an austenite-ferrite duplex stainless steel wire for forging, the metal structure of which has a ferrite phase of 20.0 to 65.0% by volume; 3. The method for manufacturing a bolt according to claim 2, further comprising a step of heating the steel wire after the wire drawing to a temperature of 50° C. or higher and 300° C. or lower, and then warm forging the steel wire into a bolt material having a head and a shaft. Md 30 (℃)=551-462(C+N)-9.2Si-8.1Mn-13.7Cr-29(Ni+Cu)-18.5Mo-68Nb...(2) However, each element symbol in the above formula (2) represents the content (mass%) of each element contained in the steel, and if the element is not contained, it is set to zero.

6. The method for manufacturing a bolt according to claim 4 or claim 5, wherein a forging austenite-ferrite duplex stainless steel wire having a diameter of 6.5 mm or more is used.

Citation Information

Patent Citations

  • Production of precipitation hardening stainless steel bolt

    JP1996311554A

  • Stainless steel wire rod for high strength product, and high-tensile bolt made of stainless steel having excellent durability

    JP2005179718A

  • T-head bolt made of austenitic stainless steel, and method for producing the same

    JP2006274295A

  • Two-phase stainless steel wire rod for high-strength highly corrosion-resistant bolt having excellent cold forgeability, steel wire, bolt and method for producing the same

    JP2009091636A

  • High-strength high-corrosion resistance stainless steel bolt excellent in stress corrosion crack resistance, and its manufacturing method

    JP2012188727A